Effect of warm footbath with vibration on arteriovenous fistula puncture-related pain in hemodialysis patients - Ali Madadi, Zahra Abbas; Azimian, Jalil; Falahatpishe, Farzaneh; Heidari, Mahmoud Alipour (International Journal of Research in Medical Sciences, 2017)
Background: Pain and stress of hemodialysis are experienced by more than 50% of patients who are suffering from renal disease; hence decreasing a part of these adverse effects can be effective on individual’s long term coping with hemodialysis. The current study was done to determine the effect of warm footbath with vibration on arteriovenous fistula puncture-related pain in hemodialysis patients. Methods: This clinical trial was conducted on 31 hemodialysis patients in 2014. The patients were selected by simple random sampling method and placed in one group. First, the pain intensity of all patients was measured in the six frequent hemodialysis sessions without any intervention (control method). After two weeks, the intervention of warm footbath with vibration was done on all patients and the pain intensity was measured for six frequent hemodialysis sessions (intervention method). The patients were received 40±2 °C footbath with vibration by foot massage spa machine for ten minutes; then, fistula needles were placed and the pain intensity was assessed by using a numerical rating scale. Data were analyzed by ANOVA and T test. Results: The study group had contained 20 males (64.5%), 11 females (35.5%), with an average age of 44.16±14.85 and a range of 18 to 65 years old, which shows that the pain intensity of the warm footbath with vibration method was lower than the control method (P< 0.05). Conclusions: Warm footbath with vibration can be used as an effective palliative method to reduce pain of hemodialysis patients.